Three-dimensional X-ray micro-computed tomography of cracks in a furnace cycled air plasma sprayed thermal barrier coating. (1st March 2015) - Ahmadian, Shayan; Browning, Alyssa; Jordan, Eric H.
Abstract : Using X-ray micro-computed tomography, a total of 3 × 3 mm 2 area of an air plasma sprayed (APS) thermal barrier coating (TBC) was imaged with a resolution of 0.76 μm at 60% cyclic furnace life. Over 10, 000 X-ray micrographs were used to extract the 3-D geometry of the cracks in the top coat. The true shape, center and location of the cracks with respect to bond coat peak–valley roughness features were obtained, which revealed the real nature of cracking characteristics of APS TBCs.